COMPARISON OF TRANSFERRIN SATURATION LEVELS IN ANEMIA OF CHRONIC DISEASE AND IRON DEFICIENCY ANEMIA: A CROSS-SECTIONAL STUDY - Andi Ayu Hafsari; Nadirah Rasyid Ridha; Ema Alasiry; Syarifuddin Rauf; Setia Budi Salekede; Kwari Januar Satriono (UNG, 2023)
About 33 percent of the global population is anemic. Anemia of chronic disease (ACD) is caused by chronic inflammation. Iron deficiency anemia (IDA) is caused by a decrease in the body's iron reserves to form red blood cells. There are many clinical and laboratory similarities between ACD and IDA, but the treatment is very different. Transferrin saturation level can be used to differentiate between the two. This research is novel because it compares transferrin saturation levels in chronic and iron deficiency anemia. This study aims to determine the transferrin saturation level in patients with ACD and IDA. This research method uses a cross-sectional study. Data taken from medical records. The sample for this study were children with ACD and IDA aged 1 month to 18 years at Wahidin Sudirohusodo Hospital, Makassar. The results showed that the mean transferrin saturation value in DKA children (19.40%) was higher than that in ADB children (5.66%). The Mann-Whitney test showed that there was a significant difference between the two groups (p=0.001) with a transferrin saturation cut-off point between the DKA and IDA groups of 6.5% with a sensitivity of 73.6%, a specificity of 72.5%, positive predictive value (PPV) of 78%, negative predictive value (NPV) of 67%, and odds ratio (OR) of 19,476 (95% CI). In conclusion, transferrin saturation levels can differentiate IDA and ACD using a cut-off point of 6.5%.